Urochloa decumbens has higher mycorrhizal colonization in degraded than in pristine areas in the Brazilian Cerrado - Leite, Matheus Roberto [UNESP]; Cassiolato, Ana Maria Rodrigues [UNESP]; Lannes, Lucíola Santos [UNESP] (FapUNIFESP (SciELO), 2019)
Brazil has extensive degraded areas, where vegetation fails to establish due to harsh soil conditions. However, some invasive species such as Urochloa decumbens are successful pioneers in such areas, but the reasons deserve investigation. Mycorrhizal fungi are abundant in Cerrado soils, and their association with plants are beneficial for their establishment in natural and degraded areas. This study investigated whether arbuscular mycorrhizal colonization of native and exotic plants in the Cerrado differs between pristine and degraded areas. We collected 135 plants from four functional groups in 68 areas and determined the percentage of mycorrhizal colonization. The invasive grass Urochloa decumbens had significantly higher colonization rates in degraded than in native areas, and higher colonization than the native species. These results are important for soil management since Urochloa decumbens is widely used in early soil restoration efforts, and for nature conservation concerning the management of invasive plants in restoration areas.
Keywords: Exotic plants; Grassland; Mycorrhiza; Native plants; Restoration